Analisis Penerapan Aplikasi SIPD Dalam Pelaksanaan Laporan Keuangan Pada Dinas Kesehatan Provinsi Sumatera Utara - Ria Agustia; Heny Triastuti KN; Shofwan Andri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The application of SIPD application in the preparation of regional financial reports is very beneficial in terms of budget planning and facilitating the preparation, transparency and accountability of financial reports as well as facilitating the supervision and evaluation of services. This study aims to determine the extent of the application of the Regional Development Information System (SIPD) in the preparation of financial reports of the North Sumatra Provincial Health Office. What are the constraints in the application of the Regional Development Information System (SIPD) in the preparation of financial reports of the North Sumatra Provincial Health Office. This study uses a qualitative phenomenological and descriptive approach. This study uses qualitative data in the form of interview results at the North Sumatra Provincial Health Office. The results of this study indicate that employees at the North Sumatra Provincial Health Office have understood the meaning of the Regional Development Information System (SIPD) financial application, as seen from their understanding of the meaning, benefits and objectives and the input data needed as well as the output of financial reports produced from the processing results. The quality of information produced from the implementation of the financial SIPD application is good, this is indicated by the fulfillment of three characteristics, namely: Timeliness, Reliability, Relevance